Construction and evaluation of a neurofeedback system using finger tapping and near-infrared spectroscopy - Takahashi, Shingo; Takahashi, Daishi; Kuroiwa, Yuki; Sakurai, Noriko; Kodama, Naoki (Frontiers in Neuroimaging, 2024)
Introduction: Neurofeedback using near-infrared spectroscopy (NIRS) has been used in patients with stroke and other patients, but few studies have included older people or patients with cognitive impairment. Methods: We constructed a NIRS-based neurofeedback system and used finger tapping to investigate whether neurofeedback can be implemented in older adults while finger tapping and whether brain activity improves in older adults and healthy participants. Our simple neurofeedback system was constructed using a portable wearable optical topography (WOT-HS) device. Brain activity was evaluated in 10 older and 31 healthy young individuals by measuring oxygenated hemoglobin concentration during finger tapping and neurofeedback implementation. Results: During neurofeedback, the concentration of oxygenated hemoglobin increased in the prefrontal regions in both the young and older participants. Discussion: The results of this study demonstrate the usefulness of neurofeedback using simple NIRS devices for older adults and its potential to mitigate cognitive decline.